Repurposing Drugs as Novel Triple-negative Breast Cancer Therapeutics - Das, Amiya; Agarwal, Pallavi; Jain, Gaurav K.; Aggarwal, Geeta; Lather, Viney; Pandita, Deepti (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Triple-Negative Breast Cancer (TNBC) is the most aggressive form of Breast Cancer (BC), with high rates of metastasis and recurrence and limited treatment options. Chemotherapy and radiotherapy, for example, have several harmful side effects, and no FDA-approved therapies are currently available. Repurposing old clinically approved drugs to target various TNBC targets is a novel method that has fewer side effects and leads to successful, low-cost drug development in a shorter amount of time. Medicinal plants containing various phytoconstituents (flavonoids, alkaloids, phenols, essential oils, tannins, glycosides, lactones) play a very crucial role in combating various types of diseases and are used in the drug development process because of having lesser side effects. Objective: The present review summarizes various categories of repurposed drugs that target multiple targets of TNBC, as well as phytochemical categories that target TNBC singly or in combination with old synthetic drugs. Methods: Literature information was collected from various databases such as Pubmed, Web of Science, Scopus, and Medline to understand and clarify the role and mechanism of repurposed synthetic drugs and phytoconstituents against TNBC by using keywords like “breast cancer”, “repurposed drugs”, “TNBC” and “phytoconstituents”. Results: Various repurposed drugs and phytochemicals that target different signaling pathways and exert their cytotoxic activities on TNBC cells ultimately lead to cell apoptosis, reducing the recurrence rate and stopping the metastasis process. Conclusion: Inhibitory effects can be seen at various levels, providing information and evidence to researchers in the drug development process. As a result, more research and investigations are needed to develop better therapeutic treatment options for TNBC.
Keywords: apoptosis